Computationally efficient design of directionally compliant metamaterials - Lucas A. Shaw (Nature Portfolio, 2019)
Designing mechanical metamaterials is challenging because of the large number of non-periodic constituent elements. Here, the authors develop an approach to design arbitrarily shaped metamaterials that is more computationally efficient by six orders of magnitude compared to other approaches.